'Nothing is what it seems': Posthumanism and late capitalism in Altered Carbon. Issue 1 (1st April 2021) - Empey, Julia A.
This article explores how class politics are interpreted within Altered Carbon, the 2018 television series based on the 2002 book of the same name by Richard K. Morgan. The series follows Takeshi Kovacs, a soldier turned rebel turned private detective, as he awakens after 250 years in stasis. Like all humans in this fictional world, Kovacs's existence, or essence, has been compressed into a small disk known as a cortical stack. Altered Carbon does not present a liberated or democratic future, instead, it demarcates how our posthuman fantasies can mimic, or fully embody, the class politics we see today in our late-capitalist society. Altered Carbon asks us to consider where the boundaries of the self and the body truly lie and how those boundaries, or lack thereof, are open for exploitation by those with financial means. We must critique how posthumanism has, or has not, taken up class. I believe this issue is most salient when we consider how class mediates our past, present and potential futures. I analyse the cortical stack itself as a posthumanist interpretation of Cartesian dualism and how that mind and body divide is central to maintaining capitalism through the alienation of the worker. Altered Carbon asks us to consider what happens when one's flesh and one's identity in and of itself become transferable and never truly one's own.